Chapter A Multilevel Approach to Urban Regional Agglomerations: A Swedish Case of Transition Paths toward a "Fossil-Free Society" by 2050 - Liljenström, Hans (InTechOpen, 2018)
This article has a focus on the changing patterns of connected urban spaces forming large super-regional aggregates made up of cities of various sizes and regional functions as well as the interconnecting space of much smaller municipalities of agricultural or forestry types of character. The multi-scalar level analysis of these connected clusters is pursued from the level of the individual to the regional, national, Nordic and EU levels. The enfolding of the regional pattern also has global connotations in terms of trade connections, but also in the context of bio-geo challenges as climate change, biodiversity depletion or food security considerations. The transition dynamics involves governance, economic, social and cultural aspects. International negotiations, as the Paris agreement on climate change and agreements at the UN level as the 17 "Sustainable Development Goals" (SDG), or agreements at the EU level, provide an international political frame to this process.